The multifaceted role of SMAD4 in immune cell function - Xinmu Cui; Yu Song; Jianfeng Han; Zhaoxin Yuan (Biochemistry and Biophysics Reports)
The Transforming Growth Factor-beta (TGF-β) signaling pathway, with SMAD4 as its central mediator, plays a pivotal role in regulating cellular functions, including growth, differentiation, apoptosis, and immune responses. While extensive research has elucidated SMAD4's role in tumorigenesis, its functions within immune cells remain underexplored. This review synthesizes current knowledge on SMAD4's diverse roles in various immune cells such as T cells, B cells, dendritic cells, and macrophages, highlighting its impact on immune homeostasis and pathogen response. Understanding SMAD4's role in immune cells is crucial, as its dysregulation can lead to autoimmune disorders, chronic inflammation, and immune deficiencies. The review emphasizes the significance of SMAD4 in immune regulation, proposing that deeper investigation could reveal novel therapeutic targets for immune-mediated conditions. Insights into SMAD4's involvement in processes like T cell differentiation, B cell class switch recombination, and macrophage polarization underscore its potential as a therapeutic target for a range of diseases, including autoimmune disorders and cancer.